A Descriptive Profile of Physical Education Teachers and Related Program Characteristics in Alberta - Mandigo, James L.; Thompson, Linda P.; Spence, John C.; Melnychuk, Nancy; Schwartz, Margaret; Dunn, Janice Causgrove; Marshall, Dru (Alberta Journal of Educational Research, 2003)
A survey of teachers and principals in Alberta was conducted to gain a descriptive profile of who is leaching physical education (PE) and to assess the relationship between PE specialists and variables associated with program delivery. A probability-sampling procedure was used to obtain a representative sample of schools. In these schools nonprobability procedures were used to recruit teachers. A total of'480 teachers' and 162 principals' questionnaires were returned. Although 50% (n=236) of PE teachers in the sample were classified as PE specialists (i.e., had either a degree, major or minor, in PE or a closely related area), there was a significant gap in the number of PE classes being taught by division. Of the 1,219 PE classes surveyed in this study, PE specialists taught 49% and 55% of classes at the elementary levels (Divisions I & 11) compared with 91% of junior high (Division III) and 90% of secondary (Division TV) PE classes. Significant differences were found between PE specialists and non-PE specialists on a number of items including perceptions of preparedness, teaching enjoyment and competence to teach PE, the number of PE specialists across grade levels, and the percentage of time devoted to PE in the timetable. Implications with respect to implementing PE specialists across all grades and the need for future pedagogical research to investigate the effect of PE specialists are also discussed.